FRI0025 A crucial role for lectin-like oxidized ldl receptor-1 on joint inflammation in ra. (23rd January 2014) - Ishikawa, M.; Ito, H.; Furu, M.; Murata, K.; Shibuya, H.; Yoshitomi, H.; Matsuda, S.; Nakmura, T.; ,
Abstract : Background: Rheumatoid arthritis (RA) is one of the immune-mediated inflammatory diseases. LOX-1 (Lectin-like oxidized low-density lipoprotein receptor 1), one of functional receptors for oxidized LDL (ox-LDL), is expressed in various cells, including endothelial cells and chondrocytes, and its expression is enhanced by oxidative stress, inflammatory cytokines (1 ). Several studies have reported that the ox-LDL/LOX-1 axis modulates cartilage degradation in RA (2 ) (3 ). Although the importance of LOX-1 in RA is apparent, little is known whether LOX-1 is expressed in the RA synovium, which is a major site of systemic inflammation in RA. Objectives: In this study, we investigate the presence of LOX-1 protein in human synovium, and the functional roles of LOX-1 in the pathogenesis of RA. Methods: Synovial tissues samples with RA patients were prepared at the total knee replacement. Ox-LDL was injected into the knee joints of mice with or without of anti-LOX-1 antibody. Results: The ox-LDL and LOX-1 (Figure 1) protein were clearly identified and colocalized in the synovial tissues in RA joints, particularly in the lining layer and around blood vessels. To assess the role of ox-LDL and LOX-1 in the pathogenesis of arthritis in vivo, ox-LDL, native LDL, or PBS were injected into right knee joints for 7 days and evaluated joint inflammation. Hematoxylin-eosin staining revealed that treatment with ox-LDL caused massive synovial hyperplasia, compared with the controls (Figure 2). In contrast, joints pretreated with the anti-LOX-1 antibody significantly inhibited synovial hyperplasia induced by ox-LDL treatment. Immunohistochemistry study showed prominent LOX-1 and MCP-1 expression (Figure 3, 4) in the cartilage and synovium in the ox-LDL-treated group, whereas the control groups hardly displayed any positive staining. Conclusions: These findings clearly demonstrated that ox-LDL/LOX-1 axis induces synovial inflammation. Therefore, blockade of LOX-1 signal would be beneficial for prevention of the synovial inflammation in the inflammatory arthritis, such as RA. References: Sawarura T, et al. Nature 1997; 386 Nakagawa T, et al. Arthritis Rheum 2002; 46, 2486-94. Kakimuma T, et al. Arthritis Rheum 2004; 50, 3495-503. Disclosure of Interest: None Declared